2008
DOI: 10.1002/da.20406
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory and confirmatory factor analysis of the Multidimensional Anxiety Scale for Children among adolescents in the cape town metropole of South Africa

Abstract: There are no published data on the factor structure of the Multidimensional Anxiety Scale for Children (MASC) among adolescents in the Cape Town metropole of South Africa. The objectives of this study were (i) to establish the exploratory factor structure of the MASC using a principal components exploratory factor analysis (EFA); (ii) to confirm the derived factor structure using confirmatory factor analysis (CFA); and (iii) to examine gender, age, and race effects among adolescents in the Western Cape of Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…It was also noted in the study that female students showed more symptoms of anxiety, depression and stress compared to their male counterparts, which was consistent with previous findings (Nuran and Nazan, 2008;Chaturaka et al, 2010). Several possible factors may explain this difference which include hormonal (Stroud et al, 2002), social pressure differences related to social competence and body image, and sociocultural norms that encourage boys to minimize certain symptoms (Fincham et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It was also noted in the study that female students showed more symptoms of anxiety, depression and stress compared to their male counterparts, which was consistent with previous findings (Nuran and Nazan, 2008;Chaturaka et al, 2010). Several possible factors may explain this difference which include hormonal (Stroud et al, 2002), social pressure differences related to social competence and body image, and sociocultural norms that encourage boys to minimize certain symptoms (Fincham et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Girls reported higher levels of anxiety symptoms on all scales of the MASC than boys in American [6,13], Chinese [12], Icelandic [14], and South African [15] studies of children and adolescents, although no gender difference in the level of harm avoidance was found in Swedish adolescents [16]. Meanwhile, females reported a significantly higher level of worry/ oversensitivity on the RCMAS than males [11].…”
Section: Introductionmentioning
confidence: 95%
“…Meanwhile, females reported a significantly higher level of worry/ oversensitivity on the RCMAS than males [11]. However, differences across various age ranges are mixed [6,12,[14][15][16]. Meanwhile, the difference in the level of anxiety symptoms between youths living in urban and rural areas has seldom been examined.…”
Section: Introductionmentioning
confidence: 98%
“…The four-factor structure of the MASC has been consistently supported in both community and clinical samples in the United States [13][14][15][16], as well as in Icelandic schoolchildren [17], Swedish adolescents [18], Australian children [9], and South African adolescents [19]. Meanwhile, research found that the MASC has good test-retest reliability [15], internal consistency [10,[14][15][16], convergent validity [16,20], and discriminant validity [16,21].…”
Section: Introductionmentioning
confidence: 96%